Entrepreneurial motivation, performance and commitment to social responsibility: toward future research - Adamu, Isa Mohammed; Kedah, Zulkarnain; Gani, AAhad M. Osman (Inderscience, 2013)
Although the study of religion and its effects on social phenomena had received attention lately, much research in this area has excluded Islam. To date there is dearth of precious information regarding Islamic religiosity and its effects on entrepreneurial outcomes. In this exploratory study, a conceptual analysis of the effects of Islamic religiosity on entrepreneurial motivation, performance and commitment to social responsibility is considered. We suggest that Islamic rituals have the potential benefit of fostering the entrepreneurial outcomes considered and we recommend that religious practices be encouraged in the workplace